Hybridity in Action and Crossing Ethnic Boundaries in the Films Ngenest and Cek Toko Sebelah - Budi Kurniawan (Lingua Cultura, 2019)
This research observed and analyzed both films entitled; “Ngenest” and “Cek Toko Sebelah” to find the manifested hybrid Chineese related to inter-ethnic relationships by drawing on the concept of hybridity. “Ngenest” and “Cek Toko Sebelah” were two successful films that were both written and directed by Ernest Prakasa, a Chinese Indonesian, and also featured Ernest Prakasa in a leading role. Close readings of both films were conducted to identify relevant and recurring themes related to the research questions. The theoretical frameworks of hybridity and essentialism/stereotyping were used to help in gaining a deeper understanding of the essence of the films. The results indicate that race still plays an important role in othering and building ethnic boundaries. Many stereotypes and counter stereotypes against both the Chinese and pribumi exist in the films. In terms of lessening ethnic boundaries, both films present hybridity in action in the form of inter-ethnic marriage and the everyday relationships of the Chinese and other ethnic groups. Although the essentialized Chinese identities are present, they are constantly in negotiation with other identities, in forming a hybridized version of Chineseness.